Metropolitan Policing in Crisis - Clement, Matt (International Journal of Criminology and Sociology, 2024)
Ever since the killing of George Floyd in May 2020, there has been a growth in social movements resisting aspects of policing in the US and the UK. In the UK it has evolved in particular directions in response to various controversies in policing and a growing mood to resist increasingly authoritarian legislation emerging from government, in part to repress the very movements they are bringing forth. This paper was delivered as part of an ESRC-funded ‘Festival of Social Science’ run at Royal Holloway University of London in November 2023 under the theme ‘Is it a crime to protest?’ and reflects on these trends as well as reviewing the need for a more critical turn in Criminology and Sociology.